Cannabinoid therapy in epilepsy. Issue 2 (April 2019) - Billakota, Santoshi; Devinsky, Orrin; Marsh, Eric
Abstract : Purpose of review: To review the history, pharmacology, and clinical science of cannabidiol (CBD) in the treatment of epilepsy. Recent findings: Phase III randomized controlled trials and prospective open label trials have provided efficacy and safety data for the use of CBD in pediatric onset severe epilepsies. The product that was studied in the vast majority of these published trials, Epidiolex (>99% of CBD and <0.10% Δ9-tetrahydrocannabinol (THC); GW pharmaceuticals, Cambridge, UK), has now been FDA approved based on this published data. Summary: Identification of CBD, Δ9-THC, and the endocannabinoid system in the mid-20th century has led to advancement of cannabis-based therapies for epilepsy. Based on clinical trial data, Epidiolex is the first CBD medication approved by a national regulatory agency (US Food and Drug Administration for Dravet and Lennox Gastaut syndrome). Approval of CBD as a treatment for these rare and severe pediatric-onset epilepsy syndromes is an important milestone, but the complete spectrum of use of cannabis-derived products, and the use of CBD for other epilepsy syndromes remains to be determined.